EFEKTIVITAS PENGGUNAAN GOOGLE FORMULIR DALAM UJIAN ONLINE BAHASA JEPANG DI SMAN 9 PEKANBARU - Tasya, Yohanna; Basri, Merri Silvia; Aristia Nst, Yenny (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract: Google Form is a system in the form of form templates that can be used for the purpose of obtaining user information. The purpose of this study was to determine the level of effectiveness of using Google Forms in Japanese online exams during the Covid-19 pandemic. Online exams are one of the alternatives used during the pandemic to avoid transmission of the corona virus. This study uses a quantitative descriptive method to describe the level of effectiveness of the use of the Google Form application in the implementation of the Online exam at SMAN 9 Pekanbaru. Sources of research data or respondents were 31 students of class 12 social studies 1 SMAN 9 Pekanbaru who took Japanese lessons and 3 teachers of SMAN 9 Pekanbaru who taught Japanese. From the results of the research analysis of the effectiveness of Google Forms in the Japanese online exam at SMAN 9 Pekanbaru, the average value of all aspects is 80% with the effective category.Key Words: Google Form, Online Exam,Covid-19